Differential Subordination and Superordination for Srivastava-Attiya Operator - Maisarah Haji Mohd; Maslina Darus (International Journal of Differential Equations)
Due to the well-known Srivastava-Attiya operator, we investigate here some results relating the p-valent of the operator with differential subordination and subordination. Further, we obtain some interesting results on sandwich-type theorem for the same.